The dynamic spatial effects of education investment on carbon emissions: heterogeneous analysis based on north-south differences in China - Dong, Yunhui; Gao, Jialin; Qiu, Jianyu; Cui, Yiniu; Guo, Mengyao (Frontiers in Environmental Science, 2024)
This article is based on panel data from 266 cities in China from 2009 to 2020. Classical economics theory and Marxist political economy theory are used as the theoretical basis for the study. Static spatial Durbin model regression and dynamic spatial Durbin model regression are conducted to analyze the impact of education investment on carbon dioxide emissions. The results show that education investment can significantly reduce carbon dioxide emissions, not only through spatial spillover effects, but also through dynamic effects over time. The implementation of education investment in one city can have a positive impact on surrounding cities, thereby achieving a certain degree of reduction in carbon emissions. Additionally, the inhibitory effect of education investment on carbon emissions is more significant in the short term.Furthermore, the study found that there is significant heterogeneity in the effect of education investment on carbon dioxide emissions between northern and southern cities, with education investment in southern cities having a more significant effect. This may be related to the industrial structure and climate of southern cities.The conclusions of this study provide useful reference for the development of education policies and environmental protection policies. In the future, the government can increase education investment appropriately to achieve the goal of reducing carbon dioxide emissions. And research has shown that education investment can suppress carbon emissions by influencing changes in energy and industrial structures. Therefore, when using measures to reduce emissions in education investment, we can focus on these two aspects.